2008
DOI: 10.1007/bf03345611
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin concentration is decreased in women with gestational diabetes mellitus in the third trimester

Abstract: ABSTRACT. Our aim is to investigate visfatin concentration and its relationship to glycated hemoglobin (HbA 1c ), insulin resistance, lipid parameters, and neonatal birth weight in women with gestational diabetes mellitus (GDM). In our study group, there were 47 women with GDM and 31 women with normal glucose tolerance (NGT) between 33-39 weeks of gestation. Plasma visfatin levels were significantly decreased in pregnant women with GDM compared to those with NGT (p=0.001). Homeostasis model assessmentinsulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
1
30
1
Order By: Relevance
“…Current evidence regarding the association of visfatin concentration with GDM is contradictory. Some studies demonstrated increased serum levels of visfatin in women with GDM (11,32,33), while others reported that visfatin concentrations were significantly lower in women with GDM (34,35). Contrary to our study, Lewandowski et al (32) and Akturk et al (35) reported a significant correlation between visfatin and HOMA.…”
Section: Discussioncontrasting
confidence: 99%
“…Current evidence regarding the association of visfatin concentration with GDM is contradictory. Some studies demonstrated increased serum levels of visfatin in women with GDM (11,32,33), while others reported that visfatin concentrations were significantly lower in women with GDM (34,35). Contrary to our study, Lewandowski et al (32) and Akturk et al (35) reported a significant correlation between visfatin and HOMA.…”
Section: Discussioncontrasting
confidence: 99%
“…Elevated plasma visfatin levels have been reported in patients with type 2 diabetes mellitus [27][28][29][30]. On the other hand, other investigative results showed decreased plasma visfatin levels in patients with type 1 diabetes, liver cirrhosis, exercise in type 2 diabetes, and in the 3 rd trimester of gestational diabetes [31][32][33][34][35]. Elevated visfatin levels were found in hemodialysis patients [36] and a positive correlation of visfatin levels with all stages of chronic kidney disease was observed [37].…”
Section: Discussionmentioning
confidence: 99%
“…Normal pregnancy is associated with alterations in maternal circulating visfatin concentrations [24,31,50,65,70,99]. In addition, gestational diabetes mellitus [5,11,37,42,66], preeclampsia [4,17,24,107], large-for-gestational-age neonate [66], fetal growth restriction [16,47] and preterm labor [53] were linked to changes in circulating maternal visfatin concentrations when compared to normal pregnant women. Consistent with these findings, patients with intraamniotic infection/inflammation have a higher amniotic fluid concentration of visfatin than those without intra-amniotic infection/inflammation [63].…”
Section: Maternal Visfatin In Normal Gestation and In Complications Omentioning
confidence: 99%